Menangkap Photographic Moments di Pelelangan Ikan Muara Baru melalui Pendekatan Komposisi dan Etnografi Fotografi - Tan Sri Zulfikar Yusuf; Dea Rifia Bella (Program Studi Penerbitan, Politeknik Negeri Jakarta, 2024)
In photography studies, composition is essential in capturing images to arrange visual elements within the photo frame. There are at least nine compositions that we analyze in this paper. These compositions are important for communicating the message the photographer wants to convey to the audience, thus creating a dialogic communication effort. This paper uses traders at the Fish Auction in Muara Baru, Jakarta, as the subject of photography, and the resulting photos become photographic moments in photographic ethnography. By capturing photographic moments through the correct composition, this paper demonstrates that photographs can produce meaning from the moments captured by the camera. This study is called visual ethnography, in which ethnographic photography is included as a sub-discipline that emphasizes the interpretive aspect of the subject's and object's expression in photos. Photographs with adjusted composition are not only seen as objects without meaning, but also as subjects that convey the expression of meaning and cultural communication. This can be a way for anthropologists and communication scholars to understand the socio-cultural phenomena of the communities being studied. The research in this paper finds that the combination of photography studies on composition and the method of ethnographic photography is still rarely undertaken, even though the study of photographs as both subjects and objects can provide a comprehensive picture of 'socio-cultural' conditions.